Preliminary assessment of the effect of trapeze postures on righting force in sailing - Tsujimoto, N.; Takeuchi, Y.; Yamamoto, H. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
This study examined the effect of change of "Trapeze" postures in sailing on the horizontal force for righting the boat. Three healthy university sailors participated. The subjects were instructed to successively change their trapeze posture. The traction force of the wire was measured from which its horizontal component for righting the boat (FH) was computed. A distinct change of FH was observed when the subjects extend their legs during trapezing. From this result, it can be suggested that the change of the trapeze posture by extending the leg linked to expand the angle between the wire and mast, thereby contributing to the increase the resultant FH.